2014
DOI: 10.1134/s1063785014090296
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cathode deuteration on the parameters of vacuum-arc plasma

Abstract: A source of ions based on vacuum discharge is the main element of vacuum neutron generators (neutron tubes) [1]. The electrodes of this source-cathode and anode-contain the working gas (hydrogen isotopes) in occluded state. The evolution of deuterium and for mation of its ions takes place upon the initiation of a short time (~1 μs) spark arc discharge between the cathode and anode. This discharge is accompanied by erosion of the surface of electrodes, which leads to the generation of working gas ions and is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 12 publications
(17 reference statements)
2
28
0
Order By: Relevance
“…Equa tions (6) were written for Ti n and Al n components with n = 0, 1, …, 4. Despite the simplified approach to describing ionization, these calculations of the com position of the ionized arc plasma give results that are quite consistent with the experimental data [7,10,13] and with detailed kinetic calculation data [14]. This allows us to hope that the proposed simple method will also yield at least qualitatively correct results for a dis charge plasma with a composite cathode.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Equa tions (6) were written for Ti n and Al n components with n = 0, 1, …, 4. Despite the simplified approach to describing ionization, these calculations of the com position of the ionized arc plasma give results that are quite consistent with the experimental data [7,10,13] and with detailed kinetic calculation data [14]. This allows us to hope that the proposed simple method will also yield at least qualitatively correct results for a dis charge plasma with a composite cathode.…”
supporting
confidence: 79%
“…In addi tion, the results of Zhirkov et al [2,9] show that ions of various sputtered components have almost identical velocities. The results of our recent model calculations [10] for a three component plasma showed that the drift velocities of ions with even significantly different masses (zirconium and deuterium) exhibit leveling as a result of strong ion-ion interaction in a dense near cathode plasma. For this reason, the proposed model assumes that ions of different components have the same velocity and, hence, the plasma can be described using the two temperature single fluid approximation for ions with effective mass m i = m Ti (1 -x) + m Al x.…”
mentioning
confidence: 97%
“…If due to some treatment the mixture of elements is improved then the ions of the different elements can be produced in one cathode spots. In this case the ions of different mass will have the same average velocity due to very strong ion-ion collision in dense cathode spot plasma [10]. In the framework of the model of [11] the calculated average velocity of Zn-Pb plasma was 0.61*10 6 cm/s for all ion types.…”
Section: Resultsmentioning
confidence: 90%
“…The maximum peak of spectrum is displaced from Zr 3+ to Zr 2+ , and the share of Zr 4+ ions significantly decreases. Such a behavior of the average Zr ion charge under deuteration of cathode was pre dicted in the framework of model [5] based on the ecton functioning mechanism of cathodic spots in a vacuum arc [6][7][8][9]. According to the results obtained within this model, a decrease in the average charge of Zr ions is caused by the additional energy spent on the ionization of deuterium atoms.…”
Section: Plasma Mass Charge Composition Of a Vacuum Arc With Deuteriumentioning
confidence: 99%